ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL TRIGONOMETRI SISWA KELAS XI SEMESTER 1 SMA PGRI 1 PURWAKARTA - Rizki Mulyawati; Nelly Fitriani (IKIP Siliwangi, 2020)
The problem discussed in this study is to find and analyze the error factors experienced by students in solving trigonometric problems. The subjects in this study were selected by purposive sampling. Where the subjects sellection based on the student’s ability that divided into 3 levels, high ability, medium ability and low ability. There are 3 subjects in total. The research method used in this study is case study method, and the research approach is qualitative research. The process of collecting data includes several methods, namely the documentation method, the method of testing the description as many as 5 problem descriptions, and the interview method. Then the steps in analyzing the data results are based on Anderson's mathematical knowledge dimensions which include 4 dimensions of knowledge, namely factual, procedural, conceptual and metacognition dimensions. The results obtained in the study were obtained from 5 problems description given based on the difficulty index of each item, students had difficulty in the type of questions number 3 and number 4, each getting a difficulty index of 0.25 which proves that all of the questions included hard. Difficulties experienced by students are in the dimensions of procedural knowledge and metacognition. In problem type number 3 students have difficulty in solving trigonometric problems in the form of states of graphs in the form of trigonometric functions students have different difficulties, namely in determining the types of trigonometric functions, reading graphs of trigonometric functions, and determining the elements contained in the student's chart still don't understand. In question type number 4 students have difficulty in trigonometric questions in the form of proof of trigonometric identity. In its completion students experience difficulties in several types of errors, such as understanding the concept of trigonometric identity, lack of student memory on types of trigonometric identities, and lack of student accuracy in completing forms of completion.